Water Quality Assessment of Former Tin Mining Lakes for Recreational Purposes in Ipoh City, Perak, Malaysia - Mohmadisa Hashim; Nasir Nayan; Yazid Saleh; Hanifah Mahat; Wee Fhei Shiang (Indonesian Journal of Geography, 2018)
A study of the water quality of the former tin mining lakes in Ipoh City was carried out to determine the Water Quality Index (WQI) and classification based on the Malaysia National Water Quality Standards, in order to determine its suitability to be developed as a water recreation area. Five former mining lakes were chosen: Gunung Lang, Taman Indah, Kg. Temiang, Lahat and Kg. Engku Husin. The parameters measured were pH, dissolved oxygen, suspended solids, biochemical oxygen demand, chemical oxygen demand and ammonical nitrogen (NH3N), while the heavy metals measured were lead (Pb), copper (Cu), zinc (Zn) and arsenic (As). The analytical study shows that four former mining lakes in this research are suitable to be developed for water recreation purposes as they are classified under class II with a WQI greater than 81, which holds a clean status. Only one lake, Kg. Engku Husin, is categorised as class III, which requires an intensive treatment before it can be used for recreational purposes. Meanwhile, heavy metals such as Zn, As and Cu were at the standard level except for Pb, which exceeded the set guidelines. The local authorities and project developers should take appropriate measures to ensure that this former mining lake is well maintained and managed so that it is preserved and suitable to be developed as a recreational area.